2011
DOI: 10.1136/gut.2010.236620
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain microstructure assessed by diffusion tensor imaging in patients with chronic pancreatitis

Abstract: The findings suggest that microstructural changes of the brain accompany pain in CP. The changes are likely to be a consequence of ongoing pain and structural reorganisation of the neuromatrix as also seen in other diseases characterised by chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 50 publications
0
40
0
1
Order By: Relevance
“…These advances should be credited to pioneering studies from Denmark 73-78 and the Netherlands, [79][80][81] in which investigators systematically characterized cortical activity and morphology in numerous studies including in patients with chronic pancreatitis and healthy individuals as controls (Figure 4). Owing to these studies, we know that patients with chronic pancreatitis exhibit a number of features: central hyper algesia, as indicated by remote hyperalgesia to electric or heat stimulation; 73 impaired descending inhibitory pain and diffuse noxious inhibitory control; 73 an altered brain resting activity and rhythmicity on electroencephalogram as evidenced by increased activity in the lower frequency bands δ (1.0-3.5 Hz) and lower peak α frequency; 74,80 altered contact heat-evoked potentials with prolonged latencies; 75,76,82 altered brain microstructure as assessed via diffusion tensor MRI in brain regions such as the amygdala, cingulate cortex, insula, prefrontal and secondary sensory cortex; 83 and altered brain macrostructure, that is, reduced cortical thickness in the secondary somatosensory cortex, prefrontal cortex, frontal cortex, mid and posterior cingulated cortex regions as assessed via MRI (Figure 4). 84 Such studies have therefore provided a basis for our understanding of central neuroplasticity.…”
Section: Human Cns Plasticity: Lessons For Animal Studiesmentioning
confidence: 99%
“…These advances should be credited to pioneering studies from Denmark 73-78 and the Netherlands, [79][80][81] in which investigators systematically characterized cortical activity and morphology in numerous studies including in patients with chronic pancreatitis and healthy individuals as controls (Figure 4). Owing to these studies, we know that patients with chronic pancreatitis exhibit a number of features: central hyper algesia, as indicated by remote hyperalgesia to electric or heat stimulation; 73 impaired descending inhibitory pain and diffuse noxious inhibitory control; 73 an altered brain resting activity and rhythmicity on electroencephalogram as evidenced by increased activity in the lower frequency bands δ (1.0-3.5 Hz) and lower peak α frequency; 74,80 altered contact heat-evoked potentials with prolonged latencies; 75,76,82 altered brain microstructure as assessed via diffusion tensor MRI in brain regions such as the amygdala, cingulate cortex, insula, prefrontal and secondary sensory cortex; 83 and altered brain macrostructure, that is, reduced cortical thickness in the secondary somatosensory cortex, prefrontal cortex, frontal cortex, mid and posterior cingulated cortex regions as assessed via MRI (Figure 4). 84 Such studies have therefore provided a basis for our understanding of central neuroplasticity.…”
Section: Human Cns Plasticity: Lessons For Animal Studiesmentioning
confidence: 99%
“…There is extensive evidence that abnormalities exist in the brains of chronic musculoskeletal pain patients in gray matter (GM) volume/thickness 13,15,27,40,44,49,57,61 , GM density 7,9,60,62,64,65 , and both acute pain-related 16,19 and resting state 8,28,38,43 functional activity. While some work has been published regarding the relationship between chronic pain disorders and neural white matter (WM) 12,18,21,25,26,44,45,50,72,73 , only one study 50 has used contemporary analysis approaches to compare measures of anisotropy and diffusion specifically within between chronic musculoskeletal pain patients with temporomandibular disorder (TMD) and healthy volunteers. Moayedi and colleagues showed that patients have highly significant clusters of lower fractional anisotropy (FA) and higher radial diffusivity (RD) in the trigeminal nerves, right internal capsule, right external/extreme capsule, and diffusely throughout other brain regions 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Гістологічні та нейрофізіологічні дослідження механізму болю показали його зв'язок з нервовим уш-кодженням, що призводить до виникнення вісцеральної гіперчутливості з сенсибіліза-цією центральної нервової системи і реор-ганізацією відділів мозку, які беруть участь в обробці вісцерального болю. Однак механіз-ми, які лежать в основі функціональних та структурних змін, вивчені недостатньо [2,3].…”
Section: вступunclassified